Development of big data visualisation tools for e-Learning - Jenissa, Kezia (2018)
Data visualisation is widely used by organisations to analyse consumer behaviour or make highly informed decisions quickly. An idiom says “picture speaks a thousand words”. Data correlation is hard to comprehend, unless the data is being displayed to graphs and charts. Although data visualisation has been used for data analysis in businesses and organisations, education institutions have not use data visualisation for their benefit. In this context, this project – big data visualisation tools for e-learning will reveal the hidden potential of data visualisation in academic field. There might be teachers or students that are going to have improved learning experience by utilising this project. For teachers, they can monitor the students’ easily other than via face to face interaction. For students, they can have more motivation in continuing their e-learning course progress. After a detailed market research, there is definitely a gap on this kind of platform to help teachers and students to be informed of their progress. Hopefully, it will be a platform where student can be more eager to continue their study progress, and teachers can be more aware of their class performance and ease the academic supervision.